1995
DOI: 10.1108/09564239510096894
|View full text |Cite
|
Sign up to set email alerts
|

Level of success inputs for service innovations in the same firm

Abstract: A review shows most of these studies are case or industry specific, address the basic nature of service, are limited to consumer services, or address specific components of the service delivery area. Two exceptions to this are:(1) empirical finding of a dependence on innovations in service industries (Parasuraman and Varadarajan, 1988); and (2) the application of concept testing to new service development (Murphy and Robinson, 1981). However, our review suggests that none of these addresses the process itself … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(7 citation statements)
references
References 56 publications
0
7
0
Order By: Relevance
“…Based on S-D logic, Ordanini and Parasuraman (2011) propose a conceptual framework of service innovation, and empirically verify the effects of frontline employee involvement on the outcomes of organizations' service innovation programs. Prior research has also found that frontline employee involvement improves new service development outcomes (de Brentani, 2001;Martin & Horne, 1995). For instance, Hartline (2010, 2013) verify its effect on service marketability, which is one aspect of these outcomes.…”
Section: Frontline Employee Involvement and Healthcare Service Innova...mentioning
confidence: 95%
See 1 more Smart Citation
“…Based on S-D logic, Ordanini and Parasuraman (2011) propose a conceptual framework of service innovation, and empirically verify the effects of frontline employee involvement on the outcomes of organizations' service innovation programs. Prior research has also found that frontline employee involvement improves new service development outcomes (de Brentani, 2001;Martin & Horne, 1995). For instance, Hartline (2010, 2013) verify its effect on service marketability, which is one aspect of these outcomes.…”
Section: Frontline Employee Involvement and Healthcare Service Innova...mentioning
confidence: 95%
“…Studies on frontline employee involvement in innovations are primarily situated in the field of service innovation or new service development. They have indicated the relationship of frontline employee involvement with innovation outcomes, such as innovation success (de Brentani, 2001;Martin & Horne, 1995), and innovation volume and radicalness (Ordanini & Parasuraman, 2011), but not with innovation quality. Research of top management involvement in innovations has covered the domains of service innovation and NPD.…”
Section: Theoretical Framework and Hypotheses Developmentmentioning
confidence: 99%
“…Innovation is presumed to be the sole province of service producing enterprises, even though the interaction with the customer -as described above -is an important part of the service innovation process and, of course, a key success factor of new services [30,31]. This suggests that new NSD models should incorporate the mechanism of customer-producer interactions as well as strategies to be successfully implemented [32] within value innovative new services.…”
Section: The Commercialization Of Servicesmentioning
confidence: 99%
“…The collaborative dimension captures the extent to which the customer is participating in the creation of the offering (Alam, 2002;Ives & Olson, 1984;Marsden & Littler, 1996;Martin & Horne, 1995). In service innovation, Martin and Horne (1995) separate two constructs in customer participation: direct customer participation in the process, and indirect participation, in which the internal information about the customer is used.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…However, despite a widespread recognition in the literature, companies still fail to integrate the customer into the innovation process (Martin & Horne, 1995;Matthing, Kristensson, Gustafsson, & Parasuraman, 2006;Olson & Bakke, 2001) and customers are mainly given a passive role: the service provider is expecting them to do little beyond buying and consuming offerings (Heinonen et al, 2010;Prahalad & Ramaswamy, 2000;Sanders & Stappers, 2008).…”
Section: Introductionmentioning
confidence: 99%